Phase formation behavior of alkali-activated calcined clays: effects of the reactive phase and NaOH concentration. Issue 5 (2nd November 2021) - Rakhimova, Nailia R.; Morozov, Vladimir P.; Eskin, Aleksey A.
ABSTRACT: The relevance of calcined clays as sources with a great potential for non-clinker alkali-activated materials has significantly increased in recent decades. This article reports on a study to investigate how NaOH with concentrations in the 5–14 M range affects the mechanical properties, amorphous-crystalline phase transformations, and reaction product composition of alkali-activated calcined kaolinite/montmorillonite cements with reactive phases of 60% and 33%, and with the SiO2 /Al2 O3 ratios of 1.54 and 1.74. The hardened pastes based on both calcined clays exhibited the highest compressive strength up to 9.1 MPa following their activation with 8 M NaOH. The higher amorphous fraction in the calcined clay provided gradual zeolitisation/crystallisation at Na2 O/SiO2 and Na2 O/Al2 O3 molar ratios in the 0.36–0.63 and 0.56–0.98 ranges, respectively, accompanied by the deterioration of the mechanical characteristics of the samples. The zeolite content in the alkali-activated calcined clay cements with an amorphous fraction of 33% peaked for NaOH at 11 M, and the corresponding molar ratios of Na2 O/SiO2 and Na2 O/Al2 O3 were 0.85 and 1.46, respectively. The main reaction products in the studied systems determined by XRD, TG/DSC, and FTIR spectroscopy analyses were N-A-S-H and zeolite A. The properties and reaction products obtained favor the use of proposed alkali-activated cements for controlled low-strength materials.